Jamón and Halal Lessons in Tolerance from Rural Andalucía - Civantos, Christina (Amherst College Press, 2022)
Contemporary Spain reflects broader patterns of globalization and has been the site of tensions between nationalists and immigrants. This case study examines a rural town in Spain's Andalucía in order to shed light on the workings of coexistence. The town of Órgiva's diverse population includes hippies from across Europe, European converts to Sufi Islam, and immigrants from North Africa. Christina Civantos combines the analysis of written and visual cultural texts with oral narratives from residents. In this book, we see that although written and especially televisual narratives about the town highlight tolerance and multiculturalism, they mask tensions and power differentials. Toleration is an ongoing negotiation, and this book shows us how we can identify the points of contact that create robust, respect-based tolerance.